2022
DOI: 10.1096/fba.2021-00132
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor (HIF)‐1α‐induced regulation of lung injury in pulmonary aspiration is mediated through NF‐kB

Abstract: Aspiration‐induced lung injury is a common grievance encountered in the intensive care unit (ICU). It is a significant risk factor for improving ventilator‐associated pneumonia (VAP) and acute respiratory distress syndrome (ARDS). Hypoxia‐inducible factor (HIF)‐1α is one of the primary transcription factors responsible for regulating the cellular response to changes in oxygen tension. Here, we sought to determine the role of HIF‐1α and specifically the role of type 2 alveolar epithelial cells in generating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
(255 reference statements)
0
9
0
Order By: Relevance
“…Today, gastric contents aspiration is one of the most important risk factors of ALI development, especially in ICU patients [ 305 , 306 ]. Since the main characteristic of gastric contents is their low pH, the primary inductor of this model is a hydrochloric acid solution with pH value of 1.2–1.5, administered to lab animals through the trachea and leading to damage of the airways and alveolar epithelium, as well as disruption of the lung transport functions [ 307 ].…”
Section: Relevant Murine Models Of Acute Lung Injury and Pulmonary Fi...mentioning
confidence: 99%
“…Today, gastric contents aspiration is one of the most important risk factors of ALI development, especially in ICU patients [ 305 , 306 ]. Since the main characteristic of gastric contents is their low pH, the primary inductor of this model is a hydrochloric acid solution with pH value of 1.2–1.5, administered to lab animals through the trachea and leading to damage of the airways and alveolar epithelium, as well as disruption of the lung transport functions [ 307 ].…”
Section: Relevant Murine Models Of Acute Lung Injury and Pulmonary Fi...mentioning
confidence: 99%
“…Under anesthesia, mice were injected with 30 μL of acid (HCl in normal saline (NS), pH 1.25) or NS (pH 5.3, vehicle control) by deep oral pharyngeal injection. 10 For pharyngeal injection, mice were placed on a custom-designed angled platform with their incisors hung on a wire. The tongue was pulled out of the mouse using forceps, and the liquid was directly dropped into the opening of the trachea using a micropipette.…”
Section: Methodsmentioning
confidence: 99%
“…The acid component of gastric aspirates was modeled with strong HCl. Under anesthesia, mice were injected with 30 μL of acid (HCl in normal saline (NS), pH 1.25) or NS (pH 5.3, vehicle control) by deep oral pharyngeal injection . For pharyngeal injection, mice were placed on a custom-designed angled platform with their incisors hung on a wire.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent study, we studied C57BL/6 mice, hypoxia reporter mice (oxygen-dependent degradation [ODD] domain within HIF-1α [ODD-Luc]), and HIF-1α triple transgenic cKO mice specific in Type II AEC to confirm and characterize the fate of hypoxic AEC in the pathogenesis of acid aspiration–induced lung injury ( 9 ). We found that HIF-1α is critical in regulating the inflammatory response following acid aspiration–induced lung injury ( 9 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 93%
“…Based on these previous findings, we set out to determine the role of Type II AEC in the mitochondrial TCA and glycolysis processes in the presence and absence of HIF-1α following LC and acid aspiration ( 8 , 9 , 13 ). We conclude that hypoxia in mice following direct lung injury promoted the accumulation of succinate.…”
Section: Introductionmentioning
confidence: 99%